Development of cumin essential oil nanoemulsions and its emulsion filled hydrogels. (December 2018) - Rostami, Hosein; Nikoo, Alireza Mehregan; Rajabzadeh, Ghadir; Niknia, Nushin; Salehi, Sahar
Abstract: Cumin essential oil oil-in-water nanoemulsions were formulated using non-ionic surfactants (Tween 80 and Tween 20) using an ultrasonic method. Nanoemulsion preparation was optimized for parameters such as surfactant type, surfactant concentration and sonication time to achieve minimum droplet diameter with higher physical stability. Results showed that surfactant concentration had inverse relationships with droplet diameter; however, increasing sonication time in Tween 20 and Tween 80 systems had different effects on droplets diameter. A transparent, stable nanoemulsion with droplet diameter of 70 nm was prepared with Tween 80 at a concentration of 0.75%. Thermal stability analysis showed that the nanoemulsions were stable when heated to 65 °C and then cooled to 25 °C. Before development of nanoemulsion-filled hydrogels, the brittle structure of the κ-carrageenan gel (0.25%) with the highest amount of syneresis was improved by the addition of the soluble part of gum tragacanth at a concentration of 0.6%. Optically transparent filled hydrogels were formed by incorporating cumin essential oil nanoemulsions into carrageenan-tragacanth gels. The textural properties of the mixed gels did not change noticeably after the nanoemulsion droplets were incorporated. This approach may, therefore, be useful for the incorporation of various types of lipophilic bioactive agents into functional food gels. Highlights: Cumin essential oil nanoemulsions were formulated using non-ionic surfactants and water using an ultrasonic method. Droplet diameter decreased as the surfactant concentration and sonication time increased up to reaching optimum condition. κ-carrageenan gels' brittle structure was improved by the addition of the water soluble part of gum tragacanth. Nanoemulsion incorporation into the optimized mixed gel had negligible effects on textural and optical characteristics.